Weaving through a cryptic species: Comparing the Neotropical ants Camponotus senex and Camponotus textor (Hymenoptera: Formicidae) - Fox, Eduardo Gonsalves Paterson; Solis, Daniel Russ [UNESP]; Lazoski, Cristiano; Mackay, William (Elsevier B.V., 2017)
Camponotus senex (Fr. Smith 1858) and Camponotus textor Forel, 1899 are commonly confused species in the New World tropics. We provide morphological characteristics based on the larvae and adults, behavioural differences, together with evidence from molecular markers (cuticular hydrocarbon profiles, venom differences, nuclear ribosomal ITS-1, and mtDNA COI sequence comparisons) to separate the two species, demonstrating they are not immediately closely related. In conclusion we suggest new reliable morphological characters which can benefit from deeper phenetic analysis, and support the contextual usefulness of non-morphological tools in resolving sibling ant species.
Keywords: Ant systematics; Myrmecological diversity; Body hairs; Bristles; Chemotaxonomy; Molecular ecology; Cuticular waxes; Ultrastructure